2006
DOI: 10.1097/01.pas.0000213322.89670.48
|View full text |Cite
|
Sign up to set email alerts
|

Glypican 3: A Novel Marker in Testicular Germ Cell Tumors

Abstract: Glypican 3 (GPC3), a membrane-bound heparin sulfate proteoglycan, may play a role in promoting embryonic cell growth and differentiation. GPC3 is mutated in Simpson-Golabi-Behmel syndrome, characterized by tissue overgrowth and an increased risk of embryonal malignancies. Recently, GPC3 was reported to be one of the over-expressed genes in testicular yolk sac tumors by gene expression microarray analysis. However, the presence of the GPC3 protein in germ cell tumors has never been investigated. The purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
127
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(138 citation statements)
references
References 37 publications
9
127
1
1
Order By: Relevance
“…In addition, we observed that a-fetoprotein staining was sometimes associated with background staining, similar to that observed in gonadal yolk sac tumors, 10,11,16,17 making it difficult to interpret. Recently, glypican-3 has been described as a novel marker for testicular yolk sac tumors, 18 but its experience in primary yolk sac tumors of the CNS is very limited, with only two cases studied. 19 In our study, all 27 yolk sac tumors were positive for glypican-3; however, 12 of 27 (44%) yolk sac tumors showed staining in o60% of the tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we observed that a-fetoprotein staining was sometimes associated with background staining, similar to that observed in gonadal yolk sac tumors, 10,11,16,17 making it difficult to interpret. Recently, glypican-3 has been described as a novel marker for testicular yolk sac tumors, 18 but its experience in primary yolk sac tumors of the CNS is very limited, with only two cases studied. 19 In our study, all 27 yolk sac tumors were positive for glypican-3; however, 12 of 27 (44%) yolk sac tumors showed staining in o60% of the tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions with the Wnt pathway, whose primary ligands are differentially-expressed in a tissue-specific manner, may account for these opposed observations. Zynger et al, reported GPC3 expression in testicular germ cell tumors [24]. All 24 yolk sac tumors (YST) and all 7 choriocarcinoma components were immunoreactive for GPC3, whereas only 38% of teratomas with immature elements and 8% of embryonal carcinomas expressed GPC3.…”
Section: Introductionmentioning
confidence: 99%
“…2,[13][14][15][16] In addition, their expression may be lost in metastases or after treatment. 17,18 Glypican-3 is a more recently identified sensitive marker for yolk sac tumor; 19,20 nevertheless, glypican-3 has also been reported in embryonal carcinoma, choriocarcinoma and teratoma. [18][19][20] Zinc finger and BTB domain containing 16 (ZBTB16), first identified in a patient with acute promyelocytic leukemia, is a zinc finger transcription factor belonging to the POZ-Krüppel family that binds to specific DNA sequences with its C-terminal zinc fingers and suppresses transcription by recruiting co-repressors with its aminoterminal POZ domain.…”
mentioning
confidence: 99%
“…17,18 Glypican-3 is a more recently identified sensitive marker for yolk sac tumor; 19,20 nevertheless, glypican-3 has also been reported in embryonal carcinoma, choriocarcinoma and teratoma. [18][19][20] Zinc finger and BTB domain containing 16 (ZBTB16), first identified in a patient with acute promyelocytic leukemia, is a zinc finger transcription factor belonging to the POZ-Krüppel family that binds to specific DNA sequences with its C-terminal zinc fingers and suppresses transcription by recruiting co-repressors with its aminoterminal POZ domain. 21,22 ZBTB16 affects diverse signaling pathways including cell cycle, differentiation, and programmed cell death pathways in hematopoietic cells and in solid tumors as well, [22][23][24][25] and is involved in major developmental and biological processes such as spermatogenesis and stem cell maintenance, hind limb formation, hematopoiesis, immune regulation, and oncogenesis.…”
mentioning
confidence: 99%